PENGEMBANGAN PEMBELAJARAN INKUIRI BERBASIS ETNOPEDAGOGI UNTUK MENGOPTIMALKAN KEMAMPUAN LITERASI DAN MODERASI BERAGAMA SISWA SEKOLAH DASAR - Nurul Mahruzah Yulia; Dewi Niswatul Fithriyah; Moh. Mualliful Ilmi (Muróbbî: Jurnal Ilmu Pendidikan, 2023)
The main and tough task in the field of education is to improve students' literacy skills and learn morality, so that it is hoped that students in Indonesia can become highly intellectual and well-behaved and moral. This research and development aims to develop literacy skills and religious moderation abilities of students at SDN Kadipaten 1. This research and development uses the ADDIE development model. With 5 stages of development and 4 types of data collection carried out namely interviews, observations, questionnaires, and tests. There are 4 indicators of literacy skills used in this study, namely reading, writing, spoken language, and linguistics. Meanwhile, indicators of the ability to moderate religion use indicators of national commitment, respecting opinions, being accommodating to local culture, and being sensitive to the surroundings. The results of this study indicate that this ethnopedagogy-based inquiry development model can be used to improve religious literacy and moderation abilities with an average ability obtained of 90% and 92%. This development is carried out by adding feedback and appreciation and reflection syntax in the development of inquiry learning.